Efektivitas Larva Black Soldier Fly (Hermetia Iilucens) dalam Mereduksi Sampah Organik - Estin Nofiyanti; Bayu Tri Laksono; Nurcholis Salman; Gatut Ari Wardani; Melly Mellyanawaty (Fakultas Teknik, 2022)
The composition of waste in Indonesia is dominated by organic waste. The waste processing process must be improved to prevent pollution in the market environment. The bioconversion process using Black Soldier Fly larvae or maggots is an effective way to process organic waste. The aim of this study was to determine the effect of feeding on the initial maggot biomass to the addition of the final maggot biomass, determine the maximum maggot weight and determine substrate consumption. This quantitative research used a completely randomized design method consist of five treatments and four replications. The various feeding between total feed and larva were A treatment (270 gram: 150 gram), B (210 gram : 150 gram), C (150 gram : 150 gram), D ( 90 gram : 150 gram) and E ( 30 gram : 150 gras). The data analysis technique used variance test and Duncan’s mean difference test. The result showed that the addition of coconut pulp feed affects to the final weight of the maggot and the value of substrate consumption. The addition of coconut dregs feed which maximally affects to the final weight of the maggot showed in A treatment which ratio coconut dregs: larva (270 gram : 150 gram). The A treatment gave an average final weight of maggot 195 grams in 18 days. The maximum reduction of coconut dregs in the bioconversion process was observed in treatment E with a substrate consumption value of 55%.